Misperception and cognition in markets - Benjamin Young (Games, 2022)
We consider a market setting where a consumer holds either a naive or sophisticated perception of their preference over products. We introduce the concept of a cognitive equilibrium, in which the consumer can transition between the cognitive states of naiveté and sophistication depending on the degree of exploitation in the market. We compare market outcomes under monopoly and competition. While competition unambiguously improves market outcomes when the consumer's cognitive state is exogenous, it can strictly lower gains from trade when cognitive states are endogenously determined.
Keywords: 330; naiveté; sophistication; cognition; markets